Antioxidant effect of grape seed extract corrects experimental autoimmune encephalomyelitis behavioral dysfunctions, demyelination, and glial activation - Mabrouk, Maha; El Ayed, Mohamed; Démosthènes, Amélie; Aissouni, Youssef; Aouani, Ezzedine; Daulhac-Terrail, Laurence; Mokni, Meherzia; Bégou, Mélina (Frontiers in Immunology, 2022)
Background and Purpose Multiple sclerosis (MS) is a multifactorial autoimmune disease of the central nervous system characterized by demyelination and chronic inflammation, as well as axonal and neuronal loss. There is no cure for MS, and despite a significant improvement of the therapeutic management of patients during the last 20 years, some symptoms are still resistant to treatment and evolution of the disease to progressive form seems still ineluctable. Aetiology of MS is complex and still not fully understood. However, inflammation is a major driver of the pathology and oxidative stress contributes to tissue injury and promotes existing inflammatory response. Despite a complex and not fully understood aetiology, oxidative stress contributes to tissue injury and promotes existing inflammatory response. Plant polyphenols are endowed with many therapeutic benefits through alleviating oxidative stress and inflammation thus providing neuroprotection in MS. We presently evaluated the curative effect of grape seed extract (GSE) in an experimental autoimmune encephalomyelitis (EAE) mice model of MS. Experimental Approach Four week-old C57Bl/6J females were subjected to EAE paradigm (using myelin oligodendrocyte glycoprotein peptide fragment (35-55), complete Freund’s adjuvant and pertussis toxin) and chronically treated with GSE from day 10 to day 30 post-induction. Clinical score and body weight were monitored daily while evaluation of sensitive, motor, cognitive and anxiety-related behaviours were performed weekly. Then, GSE effect was evaluated on whole brain and spinal cord samples through the evaluation of: oxidative stress damage, antioxidant capacities, myelin alteration, astroglial and microglial proliferation and sirtuins expression. Key results Grape seed extract curative chronic treatment corrected the clinical course of EAE, as well as the mechanical hypersensitivity and avoided the development of EAE mice thermal cold allodynia. Neuropathological evaluation showed that GSE reduced oxidative stress in the brain and spinal cord by decreasing the lipid and protein oxidation through correction of the three main antioxidant enzyme activities namely superoxide dismutase, catalase and glutathione peroxidase, as well as restoring normal myelin proteins expression, correcting microglial and astroglial proteins overexpression and sirtuins downregulation. Conclusion and implications These data strongly support GSE as an effective therapeutic approach in MS treatment.